From immobilization to recovery: Towards the development of a rapid diagnostic indicator for phosphine resistance. (January 2019) - Athanassiou, Christos G.; Kavallieratos, Nickolas G.; Brabec, Daniel L.; Oppert, Brenda; Guedes, Raul N.C.; Campbell, James F.
Abstract: The aim of this work was to evaluate the insect mobility patterns of phosphine-resistant and -susceptible adults of the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) after exposure to phosphine. Exposure bioassays were carried out at two concentrations, 1000 and 3000 ppm, while adults were observed every 15 min, for a total period of 90 min. During this observation interval, adults were visually classified as active (able to walk normally), partially immobilized (not able to walk, but showing a minimal movement), or completely immobilized (no visible movement). After the observation period, all adults were placed in a phosphine-free environment, and they again were classified as active, partially immobilized or completely immobilized. At 1000 ppm, the majority of adults of the susceptible T. castaneum population were quickly immobilized after a 15 min observation period, while in contrast, the majority of adults of the resistant T. castaneum population were still active after the termination of the 90 min interval. At 3000 ppm, the percentage of immobilized susceptible adults was increased at the 15 min observation period, while the majority of resistant adults were immobilized only after 90 min. In the post-exposure period, the vast majority of the susceptible adults were dead. In contrast, most resistant adults recovered, regardless of the concentration that had been exposed. The results of this study delineate major differences in movement in phosphine-resistant and -susceptible T. castaneum strains, and can be applied as a quick diagnostic bioassay for the evaluation of resistance to phosphine in stored product insects. Highlights: Deviations from normal movement of phosphine-exposed adults are evident after 15 min at 3000 ppm. Post-exposure, most phosphine-susceptible adults were dead, but most -resistant adults recovered. Time-to-immobilization was inversely proportional to time-to-recovery.